Does chronic oral contraceptive use detrimentally affect C-reactive protein or iron status for endurance-trained women? - Badenhorst CE; Govus AD; Mündel T (Wiley Periodicals LLC on behalf of The Physiological Society and the American Physiological Society., 2023)
PURPOSE: Chronic use of the oral contraceptive pill (OCP) is reported to increase C-reactive protein (CRP) levels and increase the risk of cardiovascular disease in premenopausal females. METHODS: A secondary analysis of data from two research studies in eumenorrheic (n = 8) and OCP (n = 8) female athletes. Basal CRP and iron parameters were included in the analysis. Sample collection occurred following a standardized exercise and nutritional control for 24 h. Eumenorrheic females were tested in the early-follicular and mid-luteal phases, and the OCP users were tested in quasi-follicular and quasi-luteal phases (both active pill periods). RESULTS: A main effect for group (p < 0.01) indicated that average CRP concentration was higher in OCP users compared with eumenorrheic females, regardless of the day of measurement within the cycle. Results demonstrate a degree of iron parameters moderation throughout the menstrual cycle that is influenced by basal CRP levels; however, no linear relationship with CRP, serum iron, and ferritin was observed. CONCLUSIONS: Basal CRP values were consistently higher in the OCP group despite participants being in a rested state. These results may indicate a potential risk of cardiovascular disease in prolonged users of the OCP when compared to eumenorrheic female athletes.
Keywords: cardiovascular risk; exercise; females; inflammation; ovarian hormones; Humans; Female; Iron; C-Reactive Protein; Cardiovascular Diseases; Ferritins; Contraceptives, Oral